Renewable energy - Şen, Zekai (Springer International Publishing AG, 2020)
Renewable energy sources are available in any part of the globe in different or combined forms that need attention for refined potentiality calculation methodologies.
Keywords: Renewable energy; Earth Systems Data Processing and Visualization Using MATLAB; Environmental Sciences; Ecology